Technology Access and Financial Stress: Post-COVID-19 Academic Outcomes for First-Generation and Continuing-Generation College Students - Besjanë Krasniqi; Susan Sonnenschein (Education Sciences, 2025)
Technology is essential in higher education, yet disparities in access disproportionately affect first-generation college students. This study examines how technology access and financial stress impact academic performance for first-generation (FGCS) and continuing-generation college students (CGCS). Students (N = 430) were asked to reflect on their experiences during the COVID-19 pandemic, particularly their technology access and financial stress. Results showed that FGCS reported significantly lower technology access and higher levels of financial stress than CGCS. Greater technology access was a significant positive predictor of academic performance for FGCS but not CGCS. However, this effect diminished when financial stress was added to the regression model. Moderation analysis showed that financial stress significantly moderated the relation between technology access and academic performance. This suggests that under high financial stress, technology access becomes a critical resource for academic performance.